Reconstruction of an effective magnon mean free path distribution from spin Seebeck measurements in thin films - Chavez-Angel, E.; Zarate, R. A.; Fuentes, S.; Guo, E. J.; Klaeui, M.; Jakob, Gerhard (New Journal of Physics, 2017)
A thorough understanding of the mean-free-path (MFP) distribution of the energy carriers is crucial to engineer and tune the transport properties of materials. In this context, a significant body of work has investigated the phonon and electron MFP distribution, however, similar studies of the magnon MFP distribution have not been carried out so far. In this work, we used thickness-dependence measurements of the longitudinal spin Seebeck (LSSE) effect of yttrium iron garnet films to reconstruct the cumulative distribution of a SSE related effective magnon MFP. By using the experimental data reported by (Guo et al 2016 Phys. Rev. X 6 031012), we adapted the phonon MFP reconstruction algorithm proposed by (Minnich 2012 Phys. Rev. Lett. 109 205901) and apply it to magnons. The reconstruction showed that magnons with different MFP contribute in different manner to the total LSSE and the effective magnon MFP distribution spreads far beyond their typical averaged values.
CRIS-Team Scopus Importer:2023-03-27
Keywords: magnon mean-free-path; MFPdistribution; spin-diffusion-length